Combining Biomarkers and Imaging for Short‐Term Assessment of Cardiovascular Disease Risk in Apparently Healthy Adults. Issue 15 (4th August 2020) - Gore, Maria Odette; Ayers, Colby R.; Khera, Amit; deFilippi, Christopher R.; Wang, Thomas J.; Seliger, Stephen L.; Nambi, Vijay; Selvin, Elizabeth; Berry, Jarett D.; Hundley, W. Gregory; Budoff, Matthew; Greenland, Philip; et al.
Abstract : Background: Current strategies for cardiovascular disease (CVD) risk assessment focus on 10‐year or longer timeframes. Shorter‐term CVD risk is also clinically relevant, particularly for high‐risk occupations, but is under‐investigated. Methods and Results: We pooled data from participants in the ARIC (Atherosclerosis Risk in Communities study), MESA (Multi‐Ethnic Study of Atherosclerosis), and DHS (Dallas Heart Study), free from CVD at baseline (N=16 581). Measurements included N‐terminal pro‐B‐type natriuretic peptide (>100 pg/mL prospectively defined as abnormal); high‐sensitivity cardiac troponin T (abnormal >5 ng/L); high‐sensitivity C‐reactive protein (abnormal >3 mg/L); left ventricular hypertrophy by ECG (abnormal if present); carotid intima‐media thickness, and plaque (abnormal >75th percentile for age and sex or presence of plaque); and coronary artery calcium (abnormal >10 Agatston U). Each abnormal test result except left ventricular hypertrophy by ECG was independently associated with increased 3‐year risk of global CVD (myocardial infarction, stroke, coronary revascularization, incident heart failure, or atrial fibrillation), even after adjustment for traditional CVD risk factors and the other test results. When a simple integer score counting the number of abnormal tests was used, 3‐year multivariable‐adjusted global CVD risk was increased among participants with integer scores of 1, 2, 3, and 4, by ≈2‐, 3‐, 4.5‐ and 8‐fold, respectively, when compared with those with a score of 0. Qualitatively similar results were obtained for atherosclerotic CVD (fatal or non‐fatal myocardial infarction or stroke). Conclusions: A strategy incorporating multiple biomarkers and atherosclerosis imaging improved assessment of 3‐year global and atherosclerotic CVD risk compared with a standard approach using traditional risk factors.